Strategi Komunikasi Dakwah Band Wali dalam Lagu Cari Berkah - Permana, Restiawan (Jurnal Komunikasi Islam, 2013)
The so-called religious songs are increasingly recognized and positively responded by many, both children and adult. They then become an alternative trend in prose–lytizing, in addition to lecturing. Wali is a musical group in Indonesia that has a commitment to spread Islamic religious symbols through the lyrics of its songs. By using descriptive analysis, this article examines the song entitled Cari Berkah by the group as a strategy of proselytizing communication. The study results show that the song has delivered a positive message in accordance with Islamic law, as the group leads the listeners to become aware of the importance of helping each other.Keywords: song lyric, proselytizing strategy, wali band, des–criptive analysis.------------------------------------------------------------------------dan digemari oleh banyak kalangan, mulai dari anak-anak hingga orang tua. Kini berdakwah melalui lagu merupakan tren alternatif, selain berceramah. Wali adalah sebuah grup musik dalam negeri yang memiliki komitmen untuk mela–kukan syiar agama melalui lirik lagu-lagunya. Melalui analisis deskriptif, artikel ini membahas lagu Cari Berkah karya Band Wali sebagai strategi komunikasi dakwah. Hasil studi menyatakan bahwa lagu Cari Berkah yang dibuat oleh Wali mewakili pesan yang positif sesuai dengan syariat Islam, karena Band Wali ingin mengajak pendengarnya untuk lebih menyadari akan arti pentingnya hidup saling tolong menolong antar sesama.Kata Kunci: syair lagu, strategi dakwah, band wali, analisis deskriptif.